Field-scale spatial variation in yields and nitrogen fixation of clover-grass leys and in soil nutrients - Nykänen, Arja; Jauhiainen, Lauri; Kemppainen, Jukka; Lindström, Kristina (MTT Agrifood Research Finland, 2008)
Biological nitrogen fixation (BNF) plays a crucial role in organic farming and red clover (Trifolium pratense) is cultivated widely in boreal grasslands for BNF. A geostatistical method, model-based kriging, was used to determine the spatial variation in yield, clover content and BNF of clover-grass leys as well as soil chemical properties throughout two fields in 2004-2006. Based on this variation, principal component analysis (PCA) was used to determine the similar patterns of variation. On one location, total dry matter yields of the leys decreased over three production years from 9 700 to 4 100 kg ha-1, clover content from 53 to 26% and BNF from 150 to 40 kg N ha-1, whereas on the other location the yields increased from 6 500 to 7 100 kg ha-1, clover content from 52 to 62% and BNF from 100 to 120 kg N ha-1. Nutrient concentrations in soil also varied greatly within the fields, although this depended on the nutrient species. Kriging combined with PCA described the spatial variation of ley parameters very informatively, but was not as powerful for describing the pattern of nutrients. Based on the spatial dependence determined in the two fields investigated, it seems that the sampling distance should be 80 m for soil nutrients, 100 m for yield and 60 m for clover content and BNF determination, respectively.
Keywords: Ka; Biological nitrogen fixation; geostatistics; kriging; pH; red clover; leys